STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) EDUCATION POLICY - Joni Wilson Sitopu; Risqah Amaliah Kasman; Muhammad Fuad (Adisam Publisher, 2025)
The STEM (Science, Technology, Engineering, and Mathematics) education policy aims to prepare the younger generation to face the challenges of the future by improving competence in these fields. The implementation of this policy involves the integration of STEM into the curriculum from an early age, as well as synergy between the government, educational institutions, and the industrial sector to provide the necessary support and resources. In addition to ensuring that the education provided is applicable, this policy also seeks to reduce the gender gap and encourage wider participation. Through comprehensive STEM education, it is hoped that an innovative workforce will be created that is ready to compete at a global level and support sustainable economic growth.